1991
DOI: 10.1073/pnas.88.8.3392
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and mutation rate of the H strain of hepatitis C virus.

Abstract: Patient H is an American patient who was infected with hepatitis C virus (HCV) in 1977. The patient became chronically infected and has remained so for the past 13 years. In this study, we compared the nucleotide and predicted amino acid sequences of the HCV genome obtained from plasma collected in 1977 with that collected in 1990. We find that the two HCV isolates differ at 123 of the 4923 (2.50%) nucleotides sequenced. We estimate that the mutation rate of the H strain of HCV is -1.92 x 10-3 base substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
346
5
8

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(376 citation statements)
references
References 29 publications
17
346
5
8
Order By: Relevance
“…High genetic heterogeneity has been noted for HCV, with a nucleotide substitution rate of 1.44暳10 -3 -1.92暳10 -3 per site per year [22] . These mutations result in diversification and evolution of different HCV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…High genetic heterogeneity has been noted for HCV, with a nucleotide substitution rate of 1.44暳10 -3 -1.92暳10 -3 per site per year [22] . These mutations result in diversification and evolution of different HCV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…2 The genetic heterogeneity of HCV is a result of the high viral replication rate of 10 10 -10 13 viral particles daily 3 together with spontaneous nucleotide substitutions of 10 À2 -10 À3 substitutions per nucleotide per year. 4,5 This suggests that vaccine development should be targeted against genetically stable regions of the HCV genome. It has been shown that DNA immunizations can induce both specific antibodies and cell-mediated responses against the structural and nonstructural (NS) HCV proteins in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a 27-amino acid region at the amino terminus of E2/NS1 has been shown to vary greatly between isolates and has become known as hypervariable region 1 (HVR). [1][2][3] The HVR appears to be structurally unconstrained and tolerates extensive amino acid variation; it probably encodes part of an envelope peptide that is exposed to the host' s immune response. 4 Studies have indicated the presence within this region of linear B-cell epitopes recognized by neutralizing antibody, and amino acid variation occurring during chronic infection has been put forward as the mechanism underlying the escape from antibody binding.…”
mentioning
confidence: 99%